2016
DOI: 10.3171/2016.4.jns16349
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery stenosis with a high-intensity signal plaque on time-of-flight magnetic resonance angiography and association with evidence of intraplaque hypoxia

Abstract: OBJECTIVE Hypoxia induces angiogenesis and plays a major role in the progression of carotid plaques. During carotid intervention, plaques with high-intensity signals on time-of-flight (TOF) magnetic resonance angiography (MRA) often cause ischemic stroke and embolic complications. However, the role of intraplaque hypoxia before carotid endarterectomy (CEA) and carotid artery stenting is not presently understood. In this study the authors aimed to investigate the relationship between intraplaque hypoxia and MRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Moreover, expression of CD34 in the intraplaque neovessels was not significantly different between the two groups. Additionally, a significantly higher rate of IPH in plaques with high-intensity on TOF-MRA was seen in the present study, and this finding was similar to a previous study's finding [11]. The arterial pericytes may play a role in vascular remodeling, calcification, and intraplaque neovascularization in advanced and complicated atherosclerotic lesions [12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, expression of CD34 in the intraplaque neovessels was not significantly different between the two groups. Additionally, a significantly higher rate of IPH in plaques with high-intensity on TOF-MRA was seen in the present study, and this finding was similar to a previous study's finding [11]. The arterial pericytes may play a role in vascular remodeling, calcification, and intraplaque neovascularization in advanced and complicated atherosclerotic lesions [12].…”
Section: Discussionsupporting
confidence: 92%
“…IPH has been reported as the principal factor for progression to unstable plaque and can be confirmed on magnetic resonance imaging (MRI) of human carotid plaques [10]. Additionally, an association between high-intensity carotid plaque on time-of-flight (TOF) magnetic resonance angiography (MRA) and IPH has been reported [11]. The present study aims to elucidate the associations between the pericytes in intraplaque neovessels and the MRA findings.…”
Section: Introductionmentioning
confidence: 82%
“…Many previous reports have noted that vessel density and vessel number are important factors associated with IPH. 10,17,19,23 The results of our study demonstrated that microvessel luminal enlargement is also a pivotal characteristic of IPH.…”
Section: Enlarged Microvessel Formation In Vulnerable Plaquessupporting
confidence: 57%
“…Some pathology studies suggested that the expression of hypoxiainducible factor-1 alpha (HIF-1a) and vascular endothelial growth factor (VEGF) is associated with IPH in carotid stenosis. 9,17 However, the detailed pathological mechanisms through which microvessels and IPH develop remain obscure.…”
mentioning
confidence: 99%
“…Recent studies have reported evidence of plaque hypoxia [10], and an inverse association of levels of hypoxia-inducible factor 1-alpha with the degree of plaque instability, suggesting that hypoxia within plaque may increase its vulnerability [11]. Based on these findings, the change in the size of intra-plaque vessels may be associated with restoration of plaque rupture/erosion by resolution of hypoxia.…”
Section: Discussionmentioning
confidence: 89%